Endoscopic Management of Infected Necrotizing Pancreatitis: an Evidence-Based Approach - Boxhoorn, Lotte (Curr Treat Options Gastroenterol, 2018)
PURPOSE OF REVIEW: Endoscopic management of infected necrotizing pancreatitis has evolved rapidly over the past years and there have been interesting innovations in this field. This review provides an update on the most recently published literature regarding endoscopic management of infected necrotizing pancreatitis. RECENT FINDINGS: A recent randomized trial demonstrated no difference in mortality and major morbidity between endoscopic and surgical step-up treatment of infected necrotizing pancreatitis. However, endoscopic therapy resulted in shorter hospital stay and less pancreatic fistulas. Various innovations have been investigated with the aim to further optimize endoscopic therapy, in particular lumen-apposing metal stents. While major stent-related complications were also reported, findings from recent studies indicated that their use was associated with higher resolution rates of walled-off necrosis compared to double-pigtail stents. Other innovations, such as the multiple gateway technique and dual-modality mode, can be considered for treatment of particular cases. Furthermore, research suggests that irrigation of walled-off necrosis can be performed by using a nasocystic tube and discontinuation of proton-pump inhibitors may be considered. SUMMARY: Endoscopic treatment should be the preferred treatment modality in patients with infected necrotizing pancreatitis who are eligible for endoscopic drainage. Although data suggests that lumen-apposing metal stents are superior to double-pigtail stents, prospective multicenter studies focusing on safety as well as long-term follow-up are first needed.